2016
DOI: 10.1021/acs.orglett.5b03434
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyrrole-Fused C,N-Cyclic Azomethine Imines and Pyrazolopyrrolopyrazines: Analysis of Their Aromaticity Using Nucleus-Independent Chemical Shifts Values

Abstract: The AgOTf-catalyzed reaction of C-2 substituted pyrrole hydrazones having an N-propargyl group was studied. The selective 6-endo-dig mode of cyclization was observed, giving rise to the formation of pyrrole-fused C,N-cyclic azomethine imine derivatives. The reaction of one azomethine imine derivative with various dipolarophiles resulted in the formation of cycloadducts having a pyrazolopyrrolopyrazine skeleton. The aromaticity of C,N-cyclic azomethine imines as well as that of pyrazolopyrrolopyrazines was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Initially, based on our previous works on the synthesis of azaheterocyclic compounds, [15] we chose N ‐propargyl‐C‐2‐substituted‐pyrroles as the starting material, synthesized as described in our previous report [16a–e] . Reaction of 13a with a base provided the indolizine derivative 15a in relatively good yield beside the allene 16 and the hydrolysis compound 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Initially, based on our previous works on the synthesis of azaheterocyclic compounds, [15] we chose N ‐propargyl‐C‐2‐substituted‐pyrroles as the starting material, synthesized as described in our previous report [16a–e] . Reaction of 13a with a base provided the indolizine derivative 15a in relatively good yield beside the allene 16 and the hydrolysis compound 17 .…”
Section: Resultsmentioning
confidence: 99%
“…4` b c d For example, Özer and co-workers reported that the reaction of pyrrole hydrazones having an N -propargyl group with different dipolarophiles in the presence of catalytic amounts of silver triflate or gold(III) chloride afforded the corresponding cycloadducts with a pyrazolopyrrolopyrazine skeleton via sequential 1,3-dipolar cycloaddition and intramolecular rearrangement. 4e The use of DMAD in the silver(I)-catalyzed sequential reaction of N ′-(2-alkynylbenzylidene)hydrazides ( I ) led to the preparation of the corresponding ( Z )-2-(isoquinolin-2-ium-2-yl)-1,4-dimethoxy-1,4-dioxo-3-(tosylimino)butan-2-ide derivatives ( II ) (Scheme 1 ). This transformation required a three-step reaction involving 6- endo -cyclization, cycloaddition, and intramolecular rearrangement.…”
Section: Table 1 Optimization Of the Reaction Condition...mentioning
confidence: 99%
“…Recently, we developed new synthetic methodologies for the synthesis of various pyrrole-fused new heterocycles using alkyne cyclization reactions [1522]. In this article, we demonstrate for the first time the concept of the cyclization of N- alkyne-substituted pyrrole esters 7 (Fig.…”
Section: Introductionmentioning
confidence: 98%